Effects of a Yoga-Based Intervention on Self-Compassion, Depression and Loneliness in Obese Adolescents - Erdoğan, Ramazan; Shafaei, Hassan (International Journal of Sport Studies for Health, 2025)
Objective: The aim of this study was to examine the effects of a yoga-based intervention on self-compassion, depression and loneliness in obese adolescents.Methods and Materials: A quasi-experimental design with a pretest-posttest framework was utilized in this research, which involved a sample of 58 male adolescents aged 15 to 17 who were classified as obese. The participants were split into two equal groups: an intervention group of 29 individuals who participated in an eight-week yoga program, and a control group of the same size. To evaluate the research variables, The Self-Compassion Scale, The Patient Health Questionnaire, and The DJGLS-6 were employed, and the data were subsequently analyzed using ANCOVA.Findings: The analysis conducted at the conclusion of the intervention revealed significant differences among all groups regarding these parameters (P